Hydraulic Conductivity of Polymer-Amended Sand-Bentonite Backfills Permeated with Lead Nitrate Solutions - Sheng-Qiang Shen; Ming-Li Wei (Advances in Civil Engineering)
Hydraulic conductivity of sand-bentonite (SB) backfills amended with polyanionic cellulose (PAC) to lead nitrate (Pb(NO3)2) solutions was evaluated experimentally in this study. PAC-amended sand-bentonite (PSB) backfills were synthesized by mixing sand-bentonite mixture with 0.3 to 1.2% dry PAC (by total dry mixture mass) and mixed with a certain weight of conventional bentonite (CB) slurry. The rheology properties including the filtrate loss, viscosity, density, and pH testes of slurry with various bentonite dosages were measured to determine the reasonable CB dosage of slurry. The slump tests on PSB backfills with various mass slurries were conducted to determine the corresponding water content of backfills with slump 125 ± 5 mm. Under the applied pressure 100 kPa, the hydraulic conductivity to Pb(NO3)2 solutions (kc) of PSB backfills with various PAC contents was evaluated based on the modified filter press (MFP) tests, to ascertain the optimum PAC content of PSB backfills when permeated with Pb(NO3)2 solutions. Index properties, including the specific gravity (Gs) and liquid limit (wL) of PSB backfills, were measured after MFP tests. The MFP tests for PSB backfills were then conducted under various applied pressures to obtain the relationship between void ratio (e) and hydraulic conductivity of backfills. Finally, the flexible-wall permeability test (FWP test) under osmotic pressure 100 kPa was conducted to verify the effectiveness of the MFP test. The results indicate that slurry with 8% bentonite dosage is the reasonable choice in slurry wall construction. PSB has lower GS and higher wL compared to SB; increasing Pb concentration leads to GS of PSB increased and wL of PSB decreased. PSB with 0.6% PAC content is supposed as the optimum proportion of backfills when permeated with concentrated Pb(NO3)2 solution. PAC adsorbs large amount of bound water, which leads to higher water content (w) and e of PSB backfills, while lead ions (Pb) cause the diffuse double layer (DDL) of bentonite compressed and e of PSB backfills reduced. The kc of PSB-0.6 remains lower than 10−9 m/s and increases less than 10 times though the Pb concentration was up to 500 mM, demonstrating that the hydraulic performance of backfills can be improved effectively in Pb(NO3)2 solution by the additive PAC. The comparison results between k from MFP tests and FWP tests show that the MFP test is an effective and easy evaluation of hydraulic conductivity of backfills.